Distributed RZF Precoding for Multiple-Beam MSC Downlink - Yang, Yang; Wang, Wenjin; Gao, Xiqi (IEEE transactions on aerospace and electronic systems, 2018)
Regularized zero-forcing (RZF) precoding can be used in multiple-beam mobile satellite communication (MSC) system downlink to combat interbeam-interference for high energy efficiency. We adopt the interference cancelation idea in approximate message passing (AMP) algorithm and propose an interference cancelation message passing (IC-MP) algorithm. To combine the virtues of both IC-MP and AMP, a hybrid message passing (H-MP) algorithm is also proposed. Simulation results show that H-MP has the best performance compared with IC-MP and AMP, and may even outperform the centralized RZF precoding.